1989
DOI: 10.1152/ajpgi.1989.256.6.g943
|View full text |Cite
|
Sign up to set email alerts
|

Transport of beta-lactoglobulin across rabbit ileum in vitro

Abstract: Intestinal transepithelial transport constitutes a major limiting step in the transfer of food protein antigens to the blood. This transport was studied in isolated rabbit ileum in Ussing chamber in vitro for the milk protein antigen beta-lactoglobulin (beta-Lg). The transepithelial passage of beta-Lg was measured by enzyme-linked immunosorbent assay (ELISA) and radiolabeled protein transfer and compared with that of the nonmetabolizable marker polyethylene glycol (PEG)-4000. When 1 mg/ml of beta-[14C]Lg or [3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 0 publications
2
24
2
Order By: Relevance
“…The jejunum (beginning 10 cm distal to the Treitz ligament) was removed, rinsed with cold saline, and mounted in the Ussing chamber, as previously described (Li et al, 1989). (Madara, 1989 (Cornell et al, 1971;Warshaw et al, 1974;Heyman et al, 1982;Marcon-Genty et al, 1989). In the present study, the rate of j3-LG absorption through rat jejunum in vitro, as determined by transfer of radioactive material, was slightly higher than that previously reported for rabbit ileum (Marcon-Genty et al, 1989).…”
contrasting
confidence: 55%
See 3 more Smart Citations
“…The jejunum (beginning 10 cm distal to the Treitz ligament) was removed, rinsed with cold saline, and mounted in the Ussing chamber, as previously described (Li et al, 1989). (Madara, 1989 (Cornell et al, 1971;Warshaw et al, 1974;Heyman et al, 1982;Marcon-Genty et al, 1989). In the present study, the rate of j3-LG absorption through rat jejunum in vitro, as determined by transfer of radioactive material, was slightly higher than that previously reported for rabbit ileum (Marcon-Genty et al, 1989).…”
contrasting
confidence: 55%
“…(Madara, 1989 (Cornell et al, 1971;Warshaw et al, 1974;Heyman et al, 1982;Marcon-Genty et al, 1989). In the present study, the rate of j3-LG absorption through rat jejunum in vitro, as determined by transfer of radioactive material, was slightly higher than that previously reported for rabbit ileum (Marcon-Genty et al, 1989). The nature of the absorbed material provides information on the intracellular processing which occurs during protein transport (Walker at al, 1972;Stern and Walker, 1984 (Armbrecht and Wasserman, 1976;Andrieux et al, 1982;Debiec et al, 1985), steroid absorption (iritani and Wells, 1966) and epithelial cell turnover (Meslin et al, 1981 ).…”
contrasting
confidence: 39%
See 2 more Smart Citations
“…For both (3-Lg and a-La, a quantitative apical-to-basal transcytosis of the proteins was quite evident. It has previously been suggested that microtubules are implicated in this transport (Marcon-Genty et al, 1989;Caillard and Tome, 1992;Caillard and Tome, 1994).…”
Section: Discussionmentioning
confidence: 99%